Preparation method and application of silicon-carbon composite negative electrode material
The cyclic properties of silicon-carbon composite anode material are formed by copolymerization and heat treatment of unsaturated organic acids, acrylate monomers, acrylamide monomers, and heat treatment. The cyclic properties of silicon-carbon composite anode material are solved by chemical vapor deposition and carbon coating. The problem of insufficient reversible capacity has achieved efficient lithium-ion battery circulation performance and capacity improvement.
Patent Information
- Application Number
- CN202411536112.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing silicon-carbon composite anode materials have low cycling performance and reversible capacity, and the preparation process of porous carbon materials is cumbersome, energy consumption is large, pore structure is unstable, and pore size distribution is insufficient.
Through unsaturated organic acids, acrylate monomers, acrylamide monomers, alkali treatment, in-situ polymerization and heat treatment, porous carbon materials with stable structure, high pore ratio and uniform pore size distribution are formed, and chemical vapor deposition is carried out. Silicon and carbon coat to form a silicon-carbon composite negative electrode material.
Improve the circulation performance and reversible capacity of silicon-carbon composite anode material. The first reversible capacity reaches more than 1800 mAh/g for the first time, and the first Coulomb efficiency reaches more than 90%. The retention rate of 100 cycles at 0.1C reaches more than 88%, effectively alleviating silicon. Volume expansion improves the cycle stability of lithium-ion batteries.
Smart Images

Figure CN119038528B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery negative electrode materials, and in particular relates to a preparation method and application of a silicon-carbon composite negative electrode material. Background Art
[0002] Porous carbon materials have shown great application prospects in the field of electrochemical energy storage due to their high specific surface area, developed pore structure, and excellent conductivity. However, the theoretical specific capacity of carbon is limited, while the theoretical specific capacity of silicon is as high as 4200mAh / g. However, due to the large volume expansion of silicon, the material structure will collapse and the electrode will peel off and pulverize, thereby affecting the cycle performance of the battery. Therefore, the preparation of silicon-carbon composite negative electrode materials by combining silicon with porous carbon is the main development trend at present. In the prior art, silicon-carbon composite negative electrode materials are generally prepared by preparing porous silicon carbon with core-shell structure and capsule structure or by vapor deposition of silicon on porous carbon. The former generally has a more complicated preparation method and poor structural controllability; the latter has a relatively simple preparation method and controllable structure, but the performance of silicon-carbon negative electrode materials depends on the structural properties of porous carbon. Porous carbon used as a silicon-carbon composite negative electrode needs to have a higher specific surface area and a stable and developed pore structure, so as to provide higher capacity space and diffusion channels for lithium-ion batteries, and alleviate the volume expansion of silicon during the adsorption-deintercalation process, so as to make the battery cycle stability better. The traditional preparation process of porous carbon materials is cumbersome and consumes a lot of energy. In order to achieve the required pore volume, it is often necessary to first carbonize and then activate the pores to expand them. The activation process consumes a lot of energy, uses a large amount of acid and alkali, and is highly corrosive to the equipment. Excessive activation can easily cause the collapse of the pore structure, that is, the pore structure is not stable enough. In addition, the uniformity of the pore size distribution of porous carbon obtained by the carbonization and then activation method needs to be further improved.
[0003] CN110224125A discloses a porous carbon-nano silicon-carbon core-shell structure material and a preparation method thereof. The core-shell structure material is based on a porous carbon material, the middle embedded layer is composed of nano silicon, and the outer layer is coated with an amorphous carbon shell. The preparation method comprises: firstly etching the pre-corroded base carbon material at medium temperature in an inert gas atmosphere, then activating at high temperature, and post-treating to obtain a porous carbon material; mixing the porous carbon material with nano silicon in a solvent and grinding to obtain a composite material; mixing the composite material with a carbon source in a solvent and spray granulating, and then heat treating in an inert gas atmosphere. The invention improves the first coulomb efficiency and material structure stability of the material. After mixing with a graphite material, a high-stability silicon-carbon composite negative electrode active material with a reversible capacity of 400 to 650 mAh / g can be obtained; however, the porosity of the porous carbon in the invention is low, the silicon loaded in the pores is limited, and its reversible capacity is low.
[0004] CN115911341A discloses a porous silicon-carbon negative electrode material, which has a core-shell structure, and includes, from the inside to the outside, a porous sparse silicon carbon core, a transition layer, a dense silicon carbon layer, and a carbon coating layer. The porous carbon of the porous silicon-carbon negative electrode material of the present invention, in which silicon particles are distributed in the gaps of the carbon skeleton structure, has a porous gap structure, which can provide excellent flexibility and mechanical strength, and can buffer the expansion and contraction stress generated by lithium ion deintercalation. The silicon particles in the porous silicon-carbon negative electrode material are reasonably distributed in the gaps between the porous carbon and the carbon particles, and have excellent comprehensive performance, effectively slowing down the expansion of the silicon negative electrode material during the cycle, controlling the capacity attenuation, and improving the cycle stability; however, the porous silicon-carbon negative electrode material prepared by the invention has better cycle performance, but the reversible capacity needs to be improved. Summary of the invention
[0005] In order to solve the above-mentioned problems in the prior art, the present invention first forms a porous carbon with a stable structure, high porosity and uniform pore size distribution through copolymerization of unsaturated organic acids, acrylate monomers, and acrylamide monomers, alkali treatment, in-situ polymerization and heat treatment, and then forms a silicon-carbon composite negative electrode material with good cycle performance and high reversible capacity through silicon deposition and carbon coating.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a silicon-carbon composite negative electrode material comprises the following steps:
[0008] (P1) Copolymerization: Unsaturated organic acid, acrylate monomer, acrylamide monomer, sacrificial saturated organic acid and initiator are dissolved in water to form a mixed solution; then the temperature is raised to react, and after cooling, a suspension containing acrylic copolymer is obtained; the molar ratio of the unsaturated organic acid, acrylate monomer and acrylamide monomer is 1: (1.2-2): (2-3);
[0009] (P2) Alkali treatment: adding an inorganic base to the suspension to adjust the pH of the suspension to 8.5-9.5, and then filtering, washing, drying, and crushing the suspension to obtain acrylic copolymer particles;
[0010] (P3) In-situ polymerization: acrylic copolymer particles and surfactants are put into a solvent to form a suspension, and then phenolic monomers, polyformaldehyde, and an alkali catalyst are added to the suspension, and the temperature is raised to carry out a polymerization reaction; after the reaction is completed, the mixture is filtered, dried, and solidified to obtain a composite resin of phenolic-coated acrylic copolymer;
[0011] (P4) Heat treatment: heat-treating the composite resin in an oxidizing gas atmosphere, washing and drying after cooling to obtain a porous carbon material; the ratio of the amount of the oxidizing gas to the amount of the composite resin is (60-90) L: 1 kg;
[0012] (P5) Silicon deposition and carbon coating: Chemical vapor deposition is performed on the porous carbon material using an organic silicon source gas, so that some or all of the nano-silicon particles are attached to the pores of the porous carbon; then a gas-phase carbon source is used for vapor deposition to form a carbon coating layer, thereby obtaining a silicon-carbon composite negative electrode material.
[0013] The present invention forms an acrylic copolymer by carrying out solution polymerization of unsaturated organic acid, acrylate monomer and acrylamide monomer in a molar ratio of 1: (1.2-2): (2-3) under the action of an initiator, wherein the side chain of the copolymer contains carboxylic acid, carboxylate and amide groups. Since a sacrificial agent saturated organic acid is added during the solution polymerization process of step (P1), the saturated organic acid has a strong hydrogen bonding force with the amide group, and is thus introduced into the interior and surface of the acrylic copolymer, so that in step (P2), the inorganic base can react with the saturated organic acid to form a water-soluble salt, and the dissolution of the salt will form pores on the surface of the acrylic copolymer, that is, acrylic copolymer particles with more active sites are formed; more active sites are conducive to in-situ polymerization in the pores and surface of the acrylic copolymer particles under the synergistic action of a surfactant in the next step (P3) to form phenolic formaldehyde, that is, to form a composite resin of phenolic formaldehyde-coated acrylic copolymer. At the same time, in step (P2), the inorganic base can also react with part of the carboxylic acid in the side chain of the acrylic copolymer to form a salt, forming an acrylic copolymer with more carboxylates in the side chain, that is, the composite resin contains more carboxylates. In the next step (P4), when the composite resin is heat-treated in an oxidizing atmosphere, the acrylic copolymer, as a thermally unstable polymer, undergoes thermal decomposition at a relatively low temperature to produce small molecular gases, which escape from the matrix to form pores; while phenolic formaldehyde is a thermally stable polymer, and the residual carbon rate is high after heat treatment, thereby forming a porous carbon skeleton; because the composite resin is formed by in-situ polymerization, it is different from physical blending, so the pores of the porous carbon skeleton obtained are more uniform. At the same time, since the side chain of the acrylic copolymer in the composite resin contains more carboxylates, in step (P4), the carboxylates react in an oxidizing atmosphere to form metal oxides and metal hydroxides, and the metal oxides and metal hydroxides are activated pore expanders, that is, the acrylic copolymer in the composite resin is both a pore forming agent and an activated pore expander in step (P4), and can be activated while carbonizing and forming pores, so it is more beneficial to the structural stability of the pores. Finally, a porous carbon material with uniform pore distribution, high porosity and stable structure is obtained. The porous carbon material is subjected to chemical vapor silicon deposition and carbon coating to form a silicon-carbon composite negative electrode material.
[0014] Furthermore, in step (P1), the molar ratio of the unsaturated organic acid, acrylate monomer, and acrylamide monomer is 1: (1.4-1.8): (2.2-2.4). In the present invention, not all ratios of unsaturated organic acid, acrylate monomer, and acrylamide monomer can be copolymerized to obtain the composite resin required for step (P4). Unsaturated organic acid is one of the main copolymer monomers with high reaction activity. If its ratio is too low, the copolymer is difficult to form; the carboxylate in the acrylate monomer can play a major role in activating and expanding the pores in step (P4); after the copolymerization of acrylamide monomer, the amide group of its side chain has a strong hydrogen bond with the sacrificial agent saturated organic acid, thereby introducing part of the saturated organic acid into the acrylic copolymer, and then after the alkali treatment to form salt, the salt dissolves to form pores on the surface of the acrylic copolymer particles, thereby providing more active sites for the subsequent in-situ polymerization. That is, the three monomers have different effects, and the copolymer that meets the requirements needs to be within the above range.
[0015] Furthermore, in step (P1), the unsaturated organic acid is at least one of acrylic acid, methacrylic acid, 3,3-dimethylacrylic acid, 4-pentenoic acid, and 5-hexenoic acid; the acrylate monomer is a sodium salt or potassium salt of an acrylic acid monomer, such as sodium acrylate, potassium acrylate, potassium methacrylate, and sodium methacrylate; and the acrylamide monomer is at least one of acrylamide, N-hydroxymethyl acrylamide, and N-isopropyl acrylamide.
[0016] Furthermore, in step (P1), the sacrificial agent saturated organic acid is a C3-C6 saturated organic dibasic acid or polybasic acid, such as adipic acid, glutaric acid, succinic acid, malonic acid, and citric acid; and the initiator is at least one of dibenzoyl peroxide (BPO) and azobisisobutyronitrile (AIBN).
[0017] Furthermore, in step (P1), the amount of the sacrificial agent saturated organic acid is 6-10% of the total mass of the unsaturated organic acid, acrylate monomers and acrylamide monomers; the amount of the initiator is 4-8% of the total mass of the unsaturated organic acid, acrylate monomers and acrylamide monomers. The amount of the initiator affects the molecular weight of the copolymer. The purpose of controlling the amount of the initiator in the present invention within the above range is to prevent the molecular weight of the copolymer from being too high.
[0018] Furthermore, in step (P1), the reaction conditions are: temperature 75-90° C., time 1.5-4 h.
[0019] Furthermore, in step (P2), the inorganic base is potassium hydroxide or sodium hydroxide; and the crushing is crushing to 200-1000 mesh.
[0020] Furthermore, in step (P3), the mass ratio of acrylic copolymer particles, surfactant and phenolic monomer is 1: (0.02-0.04): (10-15); the molar ratio of phenolic monomer to paraformaldehyde is 1: (1.5-1.6), and the molar amount of paraformaldehyde is calculated based on monomer formaldehyde; and the amount of the alkaline catalyst used is 1.5-3wt% of the phenolic monomer.
[0021] Furthermore, in step (P3), the surfactant is an organic sodium salt, such as sodium dodecyl sulfate, sodium succinate sulfonate or sodium polyoxyethylene fatty alcohol ether sulfate; the solvent is an alcohol-water mixture, wherein the concentration of the alcohol is 15-30wt%, and the alcohol is ethanol or propanol; the phenolic monomer is at least one of phenol, cresol, and xylenol; and the base catalyst is an inorganic base, such as potassium hydroxide or sodium hydroxide.
[0022] Furthermore, in step (P3), the polymerization reaction conditions are: temperature of 70-90° C., and time of 3-6 hours.
[0023] Furthermore, in step (P4), the oxidizing gas is CO2 and / or O2, preferably a mixed gas of CO2 and O2 in a volume ratio of 1: (1-2); the heat treatment condition is: keeping warm at 700-900°C for 2-4 hours. The amount of oxidizing gas is very important. In the present invention, the ratio of the amount of oxidizing gas to the amount of composite resin is (60-90) L: 1 kg. If the amount is greater than this value, the composite resin is easy to burn and the residual carbon rate is low; if the amount is too low, the activation and pore expansion effect is poor.
[0024] Furthermore, in step (P4), the washing is first acidic and then water washing to neutrality, and the acid is at least one of acetic acid, oxalic acid, and citric acid.
[0025] In step (P5), the process of vapor deposition of silicon and carbon coating is well known to those skilled in the art. If an organosilicon silicon source gas is used for vapor deposition of silicon, the amount ratio of the porous carbon to the organosilicon source gas is 1kg: 150L~300L, and the organosilicon source gas is selected from at least one of silane, disilane, trichlorosilane, silicon tetrachloride, and silicon tetrafluoride; if a gaseous carbon source is used for carbon coating, the amount ratio of the porous carbon to the gaseous carbon source is 1kg: 250L~500L, and the gaseous carbon source is selected from at least one of C1-4 alkanes, C2-4 alkenes, and C2-4 alkynes.
[0026] In a second aspect, the present invention provides a silicon-carbon negative electrode material, which is prepared by the aforementioned preparation method.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The present invention forms an acrylic copolymer by copolymerizing unsaturated organic acid, acrylate monomer and acrylamide monomer in a specific ratio. During the copolymerization process, the sacrificial agent saturated organic acid is introduced into the interior and surface of the copolymer due to its strong hydrogen bonding with the amide group; then, after alkali treatment, acrylic copolymer particles with pores on the surface and more carboxylates in the side chain are formed; the copolymer particles are then polymerized in situ to form a composite resin of phenolic-coated acrylic copolymer. The composite resin is finally heat-treated under a trace amount of oxidizing gas, and the acrylic copolymer therein first decomposes and escapes from the matrix to form pores; at the same time, the carboxylates in the side chains of the acrylic copolymer form an activator under an oxidizing gas atmosphere; that is, when the composite resin is heat-treated under a trace amount of oxidizing gas, carbonization pore formation and activation pore expansion are simultaneously achieved, so as to obtain a porous carbon material with uniform pore distribution, high porosity and stable structure, and the carbon is coated with silicon and carbon by chemical vapor deposition to finally obtain a silicon-carbon composite negative electrode material.
[0029] (2) When the silicon-carbon composite negative electrode material is used in a lithium battery, the volume expansion of silicon can be effectively alleviated, and the cycle performance and charge-discharge capacity of the lithium-ion battery can be improved. The first reversible capacity is above 1800 mAh / g, the first coulombic efficiency is above 90%, and the capacity retention rate after 100 cycles at 0.1C is above 88%. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the first cycle charge and discharge curve of a lithium battery assembled with the silicon-carbon composite negative electrode material of Example 1 at a rate of 0.1C. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0032] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0033] Example 1
[0034] (P1) Copolymerization: 4-pentenoic acid, sodium acrylate and acrylamide were first prepared into a monomer mixture with a total mass of 100 g in a molar ratio of 1:1.2:2, and then 100 g of the monomer mixture, 7 g of adipic acid and 5 g of initiator BPO were dissolved in pure water to form a mixed solution; the mixture was then heated to 85°C for reaction for 2.5 h, and cooled to room temperature to obtain a suspension containing an acrylic copolymer;
[0035] (P2) Alkali treatment: sodium hydroxide was added to the suspension and stirred for 20 min to make the pH of the suspension 9.0, and then filtered, washed with pure water twice, dried in an oven at 80°C for 24 h, and crushed to 800 mesh to obtain acrylic copolymer particles;
[0036] (P3) In-situ polymerization: 10 g of acrylic copolymer particles and 0.3 g of sodium polyoxyethylene fatty alcohol ether sulfate were added into 1000 g of ethanol-water mixture (ethanol concentration was 20 wt%) under stirring to form a suspension, and then 120 g of phenol, 60 g of polyformaldehyde and 2.5 g of sodium hydroxide were added to the suspension, and the temperature was raised to 75°C for reaction for 5 h. After the reaction was completed, the mixture was filtered and dried in an oven at 90°C for curing for 24 h to obtain a phenolic-coated acrylic copolymer composite resin (weighing 136.4 g);
[0037] (P4) Heat treatment: 100 g of the composite resin was placed in a tubular furnace, and a mixed gas of CO2 and O2 with a volume ratio of 1:1 was introduced. The amount of the mixed gas was 6 L, and the composite resin was heat treated at 800 °C for 3 h. After the heat treatment, the composite resin was cooled to room temperature, washed with acetic acid for 60 min, washed with deionized water until neutral, and then placed in an oven and dried at 90 °C for 12 h to obtain a porous carbon material.
[0038] (P5) Silicon deposition and carbon coating: 50 g of porous carbon material was placed in a CVD furnace with a rotation speed of 20 rpm. Helium was introduced at a flow rate of 5 L / min. After the temperature was raised to 600°C in a helium environment, the helium flow rate was maintained and monosilane gas was introduced at a flow rate of 0.2 L / min for chemical vapor deposition for 1 hour, so that the formed silicon particles were partially or completely attached to the pores of the porous carbon. After the silane deposition was completed, the monosilane gas was stopped, and helium was continuously introduced at a flow rate of 5 L / min to remove excess monosilane gas. Then, acetylene gas was introduced at a flow rate of 0.4 L / min and maintained at 600°C for vapor deposition for 1 hour. The carbon particles formed after the decomposition of the acetylene gas were deposited on the surface of multiple carbon pieces, forming a carbon coating layer, and finally a silicon-carbon composite negative electrode material was obtained.
[0039] Example 2
[0040] The rest is the same as Example 1, except that in step (P1), the molar ratio of 4-pentenoic acid, sodium acrylate and acrylamide is 1:1.4:2.2.
[0041] Example 3
[0042] The rest is the same as Example 1, except that in step (P1), the molar ratio of 4-pentenoic acid, sodium acrylate and acrylamide is 1:1.6:2.2.
[0043] Example 4
[0044] The rest is the same as Example 1, except that in step (P1), the molar ratio of 4-pentenoic acid, sodium acrylate and acrylamide is 1:1.8:2.4.
[0045] Example 5
[0046] The rest is the same as Example 1, except that in step (P1), the molar ratio of 4-pentenoic acid, sodium acrylate and acrylamide is 1:1.8:2.6.
[0047] Example 6
[0048] The rest is the same as Example 1, except that in step (P1), the molar ratio of 4-pentenoic acid, sodium acrylate and acrylamide is 1:2:2.8.
[0049] Example 7
[0050] The rest is the same as Example 1, except that in step (P1), the molar ratio of 4-pentenoic acid, sodium acrylate and acrylamide is 1:2:3.
[0051] Example 8
[0052] The rest is the same as Example 1, except that in step (P1), acrylic acid is used instead of 4-pentenoic acid, sodium methacrylate is used instead of sodium acrylate, and citric acid is used instead of adipic acid.
[0053] Example 9
[0054] The rest is the same as Example 1, except that in step (P4), the amount of mixed gas used is 9 L.
[0055] Comparative Example 1
[0056] The rest is the same as Example 1, except that in step (P1), the molar ratio of 4-pentenoic acid, sodium acrylate and acrylamide is 1:0.5:1.5.
[0057] Comparative Example 2
[0058] The rest is the same as Example 1, except that in step (P1), the molar ratio of 4-pentenoic acid, sodium acrylate and acrylamide is 1:2.5:4.
[0059] Comparative Example 3
[0060] The rest is the same as Example 1, except that step (P3) is omitted and replaced by: the acrylic copolymer prepared in step (P2) is mixed with a commercially available phenolic resin in a mass ratio of 1:12.6 to form a mixture, and then the heat treatment of step (P4) is performed.
[0061] Comparative Example 4
[0062] The rest is the same as Example 1, except that in step (P4), the amount of mixed gas used is 4 L.
[0063] Application Example 1
[0064] The silicon-carbon composite negative electrode material prepared in Example 1 was applied to the negative electrode of a lithium-ion battery, assembled into a lithium battery, and its electrochemical performance was tested. Specific method: Silicon-carbon negative electrode material, Super P, carbon nanotubes, carboxymethyl cellulose and styrene-butadiene rubber composite binder were mixed in a mass ratio of 80:9.8:0.2:10 to form a slurry (the mass ratio of CMC and SBR was 1:1), and the slurry was applied to a copper foil with a 200 μm thick scraper, dried in a drying room, and placed in a vacuum dryer for 12 h to prepare a silicon-based negative electrode plate; then metallic lithium was used as a counter electrode, polyolefin was used as a diaphragm, 1 mol / L LiPF6 (the solvent was a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1) was used as an electrolyte, 2% VC and 5% FEC were added to the electrolyte, and button batteries were assembled in an argon atmosphere in a Braun inert gas glove box in Germany. The battery assembled above was charged and discharged on a LAND charge and discharge tester, with a charge and discharge range of 50 mV to 1.5 V and a compaction density of 1.1 g / cm 3 After three charge and discharge cycles at a current density of 0.1 C (1 C = 1500 mA / g), rate charge and discharge tests were carried out at current densities of 1C and 5C, respectively.
[0065] Application Example 2-9
[0066] Other conditions are the same as those in Application Example 1, except that the silicon-carbon composite negative electrode materials are prepared according to Examples 2-9, respectively.
[0067] Comparative Application Examples 1-4
[0068] Other conditions are the same as those in Application Example 1, except that the silicon-carbon composite negative electrode materials are prepared according to Comparative Examples 1-4 respectively.
[0069] Testing and analysis
[0070] 1) Performance test of porous silicon-carbon composite negative electrode material: The pore size distribution of the porous carbon materials prepared in the above embodiments and comparative examples was measured by the following test methods, and the element content of the silicon-carbon composite negative electrode material was tested. The data are shown in Table 1.
[0071] Pore size distribution determination: According to the gas adsorption BET method of GB / T 19587-2017, a Tristar II 3020 fully automatic specific area and pore size analyzer produced by Micromeritics Instrument Corporation of the United States was used to perform a low-temperature nitrogen adsorption experiment on the porous carbon materials prepared in step (P4) of the embodiments and comparative examples to determine their pore size distribution.
[0072] Main element content: According to GB / T 38823-2020, the vario EL cube element analyzer from Elementar of Germany was used to test the silicon content in the porous silicon-carbon composite negative electrode material, and the HCS-801 infrared carbon-sulfur analyzer was used to test the carbon content in the porous silicon-carbon composite material.
[0073] Table 1 Performance of porous silicon-carbon composite anode materials
[0074] .
[0075] It can be seen from Table 1 that compared with the comparative example, the specific surface area and micropore ratio of the porous carbon material prepared by the preparation method of the present invention are significantly higher, with a specific surface area of up to 1800 m 2 / g or above, the pore size distribution is mainly dominated by micropores <2nm, accounting for more than 90%.
[0076] In Comparative Examples 1 and 2, the microporosity in the porous carbon material is relatively low, and the pore volume and specific surface area are also relatively low.
[0077] In Comparative Example 3, although the micropores of the porous carbon material account for a large proportion, the pore volume and specific surface area are relatively low, indicating that the overall porosity is relatively low.
[0078] In Comparative Example 4, when the content of oxidizing gas during heat treatment is too low, although the micropores of the porous carbon material account for a large proportion, the pore volume and specific surface area are low, indicating that the content of oxidizing gas during heat treatment is too low and the activation pore expansion effect is poor.
[0079] 2) Electrochemical performance test: The batteries assembled in the application example and the comparative example were charged and discharged on a LAND charge and discharge tester, with a voltage range of 50 mV to 1.5 V and a compaction density of 1.1 g / cm 3 The battery performance test data is shown in Table 2.
[0080] Table 2 Electrochemical performance test
[0081] .
[0082] It can be seen from the data in Table 2 that when the silicon-carbon composite negative electrode material prepared by the preparation method of the present invention is used in a lithium battery, its first reversible capacity is above 1800 mAh / g, the first coulombic efficiency is above 90%, and the capacity retention rate after 100 cycles at 0.1C is above 88%, indicating that the silicon-carbon composite negative electrode material prepared by the preparation method of the present invention can effectively alleviate the volume expansion of silicon and improve the cycle performance and charge and discharge capacity of lithium-ion batteries.
[0083] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A method for preparing a silicon-carbon composite negative electrode material, characterized in that: The following steps are involved: (P1) Copolymerization: Unsaturated organic acid, acrylate monomer, acrylamide monomer, sacrificial saturated organic acid and initiator are dissolved in water to form a mixed solution; then the temperature is raised to react, and after cooling, a suspension containing acrylic copolymer is obtained; the molar ratio of the unsaturated organic acid, acrylate monomer and acrylamide monomer is 1: (1.2-2): (2-3); (P2) Alkali treatment: adding an inorganic base to the suspension to adjust the pH of the suspension to 8.5-9.5, and then filtering, washing, drying, and crushing the suspension to obtain acrylic copolymer particles; (P3) In-situ polymerization: acrylic copolymer particles and surfactants are put into a solvent to form a suspension, and then phenolic monomers, polyformaldehyde, and an alkali catalyst are added to the suspension, and the temperature is raised to carry out a polymerization reaction; after the reaction is completed, the mixture is filtered, dried, and solidified to obtain a composite resin of phenolic-coated acrylic copolymer; (P4) Heat treatment: heat-treating the composite resin in an oxidizing gas atmosphere, washing and drying after cooling to obtain a porous carbon material; the ratio of the amount of the oxidizing gas to the amount of the composite resin is (60-90) L: 1 kg; (P5) Silicon deposition and carbon coating: Chemical vapor deposition is performed on the porous carbon material using an organic silicon source gas, so that some or all of the nano-silicon particles are attached to the pores of the porous carbon; then a gas-phase carbon source is used for vapor deposition to form a carbon coating layer, thereby obtaining a silicon-carbon composite negative electrode material.
2. The preparation method according to claim 1, characterized in that: In step (P1), the molar ratio of the unsaturated organic acid, the acrylate monomer, and the acrylamide monomer is 1:(1.4-1.8):(2.2-2.4).
3. The preparation method according to claim 1, characterized in that: In step (P1), the unsaturated organic acid is at least one of acrylic acid, methacrylic acid, 3,3-dimethylacrylic acid, 4-pentenoic acid, and 5-hexenoic acid; the acrylate monomer is a sodium salt or potassium salt of an acrylic acid monomer; the acrylamide monomer is at least one of acrylamide, N-hydroxymethyl acrylamide, and N-isopropyl acrylamide; and / or The sacrificial agent saturated organic acid is a C3-C6 saturated organic dibasic acid or polybasic acid; the initiator is at least one of dibenzoyl peroxide and azobisisobutyronitrile.
4. The preparation method according to claim 1, characterized in that: In step (P1), the amount of the sacrificial agent saturated organic acid is 6-10% of the total mass of the unsaturated organic acid, the acrylate monomer and the acrylamide monomer; the amount of the initiator is 4-8% of the total mass of the unsaturated organic acid, the acrylate monomer and the acrylamide monomer.
5. The preparation method according to claim 1, characterized in that: In step (P1), the reaction conditions are: temperature 75-90° C., time 1.5-4 h.
6. The preparation method according to claim 1, characterized in that: In step (P2), the inorganic base is potassium hydroxide or sodium hydroxide; and the crushing is crushing to 200-1000 mesh.
7. The preparation method according to claim 1, characterized in that: In step (P3), the mass ratio of acrylic copolymer particles, surfactant and phenolic monomer is 1: (0.02-0.04): (10-15); the molar ratio of phenolic monomer to paraformaldehyde is 1: (1.5-1.6), and the molar amount of paraformaldehyde is calculated based on monomer formaldehyde; the amount of the base catalyst used is 1.5-3wt% of the phenolic monomer.
8. The preparation method according to claim 1, characterized in that: In step (P3), the surfactant is an organic sodium salt; the solvent is an alcohol-water mixture, wherein the concentration of the alcohol is 15-30wt%, and the alcohol is ethanol or propanol; the phenolic monomer is at least one of phenol, cresol, and xylenol; and the base catalyst is an inorganic base.
9. The preparation method according to claim 1, characterized in that: In step (P3), the polymerization reaction conditions are: temperature of 70-90° C. and time of 3-6 hours.
10. The preparation method according to claim 1, characterized in that: In step (P4), the oxidizing gas is CO2 and / or O2; the heat treatment conditions are: keeping warm at 700-900°C for 2-4h.